Peningkatan Pembelajaran Aktif melalui Pengembangan Paket Media di Kelas V SD Swasta Pardamean Medan - Kania Tiur Adelia Siringoringo; Romaito Pardosi; Christi Pelita Hutagaol; Sryance Romaster Simarmata; Lidwina Dedea Ginting (CV. Akademi Merdeka, 2026)
This study was conducted at Pardamean Private Elementary School in Medan to analyze the learning process in fifth grade, particularly focusing on the level of student participation during classroom activities. This research employed a descriptive qualitative approach, with data collected through classroom observations and interviews with the fifth-grade teacher, Mrs. Situmorang. The observation results indicated that most students tended to be passive, relying heavily on teacher instructions and showing limited initiative, which led to a predominantly one-way learning process. Although the teacher had made efforts to deliver explanations optimally, student-centered activities were not fully implemented due to limited learning media, time constraints, and variations in student abilities. The learning media used were primarily textbooks and the blackboard. Based on these findings, the study formulated an initial concept of simple learning media, including flash cards, question cards, student discussion sheets, and learning modules, designed to support more interactive classroom learning. In conclusion, the study highlights the need for practical and accessible learning media to encourage active student participation and reduce teacher-centered learning in elementary school classrooms.